Within-Host Diversity of SARS-CoV-2 in COVID-19 Patients With Variable Disease Severities - Al Khatib, Hebah A.; Benslimane, Fatiha M.; Elbashir, Israa E.; Coyle, Peter V.; Al Maslamani, Muna A.; Al-Khal, Abdullatif; Al Thani, Asmaa A.; Yassine, Hadi M. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: The ongoing pandemic of SARS-COV-2 has already infected more than eight million people worldwide. The majority of COVID-19 patients are either asymptomatic or have mild symptoms. Yet, about 15% of the cases experience severe complications and require intensive care. Factors determining disease severity are not yet fully characterized. Aim: Here, we investigated the within-host virus diversity in COVID-19 patients with different clinical manifestations. Methods: We compared SARS-COV-2 genetic diversity in 19 mild and 27 severe cases. Viral RNA was extracted from nasopharyngeal samples and sequenced using Illumina MiSeq platform. This was followed by deep-sequencing analyses of SARS-CoV-2 genomes at both consensus and sub-consensus sequence levels. Results: Consensus sequences of all viruses were very similar, showing more than 99·8% sequence identity regardless of the disease severity. However, the sub-consensus analysis revealed significant differences in within-host diversity between mild and severe cases. Patients with severe symptoms exhibited a significantly (p-value 0.001) higher number of variants in coding and non-coding regions compared to mild cases. Analysis also revealed higher prevalence of some variants among severe cases. Most importantly, severe cases exhibited significantly higher within-host diversity (mean= 13) compared to mild cases (mean=6). Further, higher within-host diversity was observed in patients above the age of 60 compared to the younger age group. Conclusion: These observations provided evidence that within-host diversity might play a role in the development of severe disease outcomes in COVID-19 patients; however, further investigations is required to elucidate this association.